We'll never forget you, Roberto Clemente - Engel, Trudie (New York Scholastic Inc, 1996)
Traces the baseball career of the Puerto Rican who, though his life was cut short by a tragic accident, will always be remembered as an outstanding athlete and humanitarian, and the first Latin-American player to be voted to the Hall of Fame
Hurg
5
Keywords: Baseball players -- United States -- Biography -- Juvenile literature; Puerto Ricans -- United State -- Biography -- Juvenile literature